Technologies as a factor of information society development: socio-philosophical analysis - Скиба, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article investigates the impact of information and telecommunication technologies on the development of Information Society.